Compliance with health protocols in the banking sector facing Covid-19 - Ghavamabadi, Leila Ibrahimi; Shabab, Mitra; Dehaghi, Behzad Fouladi; Hoveizi, Farkhondeh (Frontiers in Public Health, 2023)
Background The spread of the coronavirus has become one of the current challenges in the world. Implementing health protocols in the workplace along with informing people who face them, has become a vital issue. Objective The purpose of this study was to determine the level of compliance with health protocols and measure the level of awareness, attitude and performance of bank employees while facing Covid-19. Materials and methods The data collection tool included a checklist and two questionnaires (demographic information and the other on the awareness, attitude and performance of bank staff) regarding the coronavirus. Results A total of 199 bank employees from 25 bank branches participated in the study. The results showed that in 24% of the bank branches, the staff did not use face masks. And 100% of the studied bank branches lacked proper ventilation. The mean awareness scores of female employees (94.3) were significantly higher than those of male employees (87.7). Also, the performance of female employees (93.2) was significantly better than male employees (87.2). Conclusion The results showed that to achieve proper performance in controlling and reducing the covid-19 disease among bank employees and other workers, these items are noteworthy: (1) Providing and training the correct use of protective equipment including face masks. (2) Monitoring for strict implementation of health protocols. Therefore, it is necessary to keep training and information up-to-date due to the new phenomena of this disease.